Severity of gastrointestinal side effects of metformin tablet compared to metformin capsule in type 2 diabetes mellitus patients - Mansour Siavash; Majid Tabbakhian; Ali Mohammad Sabzghabaee; Niloufar Razavi (Wolters Kluwer Medknow Publications, 2017)
Objective: This study was designed to compare the severity of gastrointestinal (GI) side effects in Type 2 diabetes mellitus (DM) patients receiving tablet or capsule forms of metformin. Methods: In this prospective interventional study, patients were evaluated from June to November 2016 at DM clinics affiliated to Isfahan University of Medical Sciences, Isfahan, Iran. Adult patients with Type 2 DM who were eligible for inclusion criteria switched from metformin tablet to metformin capsule. Hemoglobin A1c (HbA1c), GI side effects, and patient satisfaction based on visual analog scale (VAS) were assessed during a 6-week follow-up of receiving metformin capsule. Findings: One hundred and three patients were evaluated, and 75 patients participated in this study. At the baseline, 40 patients (53.3%) had GI side effects due to metformin tablet which was reduced to 16 patients (21.3%) after switching to metformin capsule (P = 0.001). There was also an improvement in HbA1c (from 7 to 6.8,P < 0.0001). The results of patients' satisfaction based on VAS and numeric rating scale indicated that in 59 patients (78.67%), GI side effects were reduced after switching to metformin capsule (mean score: 7.2 with the range of 6-9) while 16 patients stated no treatment preference. Conclusion: Switching to metformin capsule may result in less GI side effects, with no further side effect complications.